589. HOW COULD PATIENTS SUPPORT SURGEONS? ANALYSIS OF PATIENT'S SKILLS BEFORE AND AFTER OESOPHAGOGASTRIC SURGERY AND IMPACT ON QUALITY OF LIFE. (24th September 2022) - Alfieri, Rita; Turchi, Gian Piero; Pinto, Eleonora; Fabbian, Alessandro; Marano, Salvatore; Cavarzan, Marco; Riva, Marta Silvia Dalla; Da Roit, Anna; Orru, Luisa; Pilati, Pierluigi; Castoro, Carlo
Abstract: The role of hospital case volume and surgeon expertise in improving results after esophagectomy is well known. However, health-professionals expertise and hospital volume are not enough. Prehabilitation trials outlined that patient involvement is mandatory to improve adherence to therapeutic programs. This study aims to identify what are patient's modalities of dealing with postoperative course, supporting surgical outcomes with a psychological intervention and to evaluate his effect in the medium-term postoperative period. Literature analysis was conducted to identify specific patient's skills supporting the postoperative course. Sixteen peculiar dimensions were identified, considering four patients skills applied to clinical, daily activities, family and work areas. Patients textual data were collected by a sixteen-questions interview. Methodology for the Analysis of Computerized Text Data was used to identify discursive repertoires used by esophageal cancer patients. These textual data let construct a closed-ended questionnaire used to assess patient's skills in the early postoperative course. A psychological intervention aimed at enhancing competencies was conducted. Skills were re-assessed and quality of life (QOL) data were collected 9-months after intervention. In this study 28 consecutive gastroesophageal cancer patients were enrolled within a larger group of patients undergone major surgery for gastrointestinal tumours. Low/medium/high levels were detected for each of the four skills. Wilcoxon signed-rank test showed that three of the four skills levels increased after the supportive intervention. Analysis revealed no differences in relation to diagnosis, oncological treatment and demographic variables. Compared to other patients, skills levels showed no differences in gastroesophageal patients. Furthermore, quality of life at 9-months after esophagectomy was comparable to date reported in current literature in the medium-long term period after surgery for digestive tract cancer. In these preliminary data, even with poorer prognosis, gastroesophageal patients deal with major surgery side effects using the same skills levels used by other gastrointestinal cancer patients. Results show that skills evaluation during hospital stay can reveal the lacking modalities of dealing with the postoperative problems due to patients' wrong beliefs about surgical results and physical recovery. When aimed at improving surgical outcomes and based on surgeon's indications, even patients can support surgical outcomes.